Strengthening Democratic Characters in Young Citizens - Indrayati, Tri; Marzuki, Marzuki (Jurnal Ilmu Pendidikan, 2021)
This study aims to strengthen the democratic character of young citizens in an educational environment. In detail, this study's objectives are to (1) establish a democratic character for young citizens in schools, and (2) strengthen democratic character in young citizens in the classroom. This article is a descriptive study with a qualitative approach investigating the reinforcement of the democratic character of young citizens. The data were gathered using in-depth interview techniques. The validity tests consisted of three activities, namely: 1) data reduction, 2) data presentation, and 3) drawing conclusions or verification. The research results suggest that the strengthening of democratic character for young citizens has been provided through school and classroom activities. Schools play a role in strengthening students' democratic character through activities such as student council and extracurricular activities that facilitate students to develop their democratic character. Simultaneously, the teacher reinforces students’ democratic character in class while teaching. The reinforcement of democratic character is carried out so that students know that they have equal rights as students in the classroom and school